2009
DOI: 10.1016/j.ejphar.2009.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of central α1-adrenoceptors on renal responses to central moxonidine and α-methylnoradrenaline

Abstract: Moxonidine (alpha2-adrenoceptor/imidazoline receptor agonist) injected into the lateral ventricle induces diuresis, natriuresis and renal vasodilation. Moxonidine-induced diuresis and natriuresis depend on central imidazoline receptors, while central alpha1-adrenoceptors are involved in renal vasodilation. However, the involvement of central alpha1-adrenoceptors on diuresis and natriuresis to central moxonidine was not investigated yet. In the present study, the effects of moxonidine, alpha-methylnoradrenaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…On the fourth day all mice except for N group were weighted and intraperitoneal injected with NS of 15% body weight 17, 52, 53 . Drinking water was revoked and the mice were immediately weighted every hour for 8 hours.…”
Section: Methodsmentioning
confidence: 99%
“…On the fourth day all mice except for N group were weighted and intraperitoneal injected with NS of 15% body weight 17, 52, 53 . Drinking water was revoked and the mice were immediately weighted every hour for 8 hours.…”
Section: Methodsmentioning
confidence: 99%
“…15 Besides that, blockade of α1-AR has been reported to reduce the effects of renal function and hemodynamic changes induced by stimulation of renal nerve and injection of norepinephrine (NE) in the kidney. 13 Therefore, the evidence has confirmed the effectiveness of α1-AR antagonists in the treatment of kidney against renal failures such as IR injury. 16…”
Section: Introductionmentioning
confidence: 92%
“…12 It has been found that alpha1adrenoceptor (a1-AR) is one of the functionally relevant adrenoceptor subtypes in the renal vasculature of the rat. 13 In fact, adrenoceptors are G protein coupled receptors, expressing in arterioles of kidney and participate in a variety of physiological renal functions and inhibition of a1-AR exhibit preventing impact on renal injury. 14 Several lines of studies have demonstrated that blocking of a1-AR decreases the level of stressinduced pro-inflammatory cytokines such as IL-1, IL-6 and increases the production of anti-inflammatory factors such as IL-10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that alpha1-adrenoceptor (α1-AR) is the functionally relevant adrenoceptor subtype in the renal vasculature of the rat. Additionally, α1-AR blockade has been reported to attenuate renal hemodynamic and functional changes induced by renal nerve stimulation and norepinephrine (NE) injection in the kidney [ 8 ]. Concurrent administration of α1-AR antagonists (prazosin and losartan) mitigated the fall in renal hemodynamics of ARF rats, although the effects of prazosin on renal function were not examined after ischemia reperfusion [ 9 ].…”
Section: Introductionmentioning
confidence: 99%